Factores que incidieron en la violencia intrafamiliar en la niñez durante la pandemia del Covid-19 en Cayambe - Puga, Vinicio D. (2021)
This research work analyzes the violence factors that affect children and adolescents in their homes and at the same time in their family nucleus in the Cayambe canton, therefore, the question of the problem was: What are the factors that influenced in the increase in intrafamily violence in children and adolescents in the Cayambe canton ?, as an idea to defend: in the Cayambe canton there is a diversity of factors that influence intrafamily violence against girls, boys and adolescents within the homes of Cayambe.